Sort by

- Relevance
- |Time

Write f(t) = ∑(i = 0,

**k**)**c**_i t^i Since Av = λv, A^i(v) = A^(i-1)(Av...1 Answers · Science & Mathematics · 27/11/2013

...

**K**- x) = -1/(x -**K**). Then, this just integrates to -ln|x -**K**| +**C**. I hope this helps!3 Answers · Science & Mathematics · 11/10/2010

...the constant. We know that initially, v(0) = 0, so: 0 =

**C**- g*M/**k****C**= g*M/**k**v(t) = (g*M/**k**)*(exp(-**k***t/M) - 1) Now, v...2 Answers · Science & Mathematics · 29/03/2010

...the constant. We know that initially, v(0) = 0, so: 0 =

**C**- g*M/**k****C**= g*M/**k**v(t) = (g*M/**k**)*(exp(-**k***t/M) - 1) Now, v...2 Answers · Science & Mathematics · 30/03/2010

... coefficient can be calculated as follows: a₀ = (

**k****C**0) =**k**! / (0!**k**!) a₁ = (**k****C**1) =**k**! / (1! (**k**-1)!) a₂ = (**k****C**...6 Answers · Science & Mathematics · 10/09/2011

...the constant. We know that initially, v(0) = 0, so: 0 =

**C**- g*M/**k****C**= g*M/**k**v(t) = (g*M/**k**)*(exp(-**k***t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

**C**- g*M/**k****C**= g*M/**k**v(t) = (g*M/**k**)*(exp(-**k***t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

**C**- g*M/**k****C**= g*M/**k**v(t) = (g*M/**k**)*(exp(-**k***t/M) - 1) Now, v...1 Answers · Science & Mathematics · 28/03/2010

...

**k**) = -(ln**k**)/**k**. S =**k**(4(ln 5)/5 + 2(ln 10)/10) = 2.4134697x10^-23 J/**K**. (**c**) S =**k**ln 4 = 1.9139877x10^-23 J/**K**. (d) S =**k**(2(ln 2...1 Answers · Science & Mathematics · 26/03/2009

..., we can rewrite the equation of the family of circle

**C**(**k**) as:**C**(**k**) : (x+2k+5)^2 + (y - 3k/2 - 7)^2 = (25/4) (**k**+8)^2 - 337...cosine law). So at any point of intersection P, the segments**c**(**k**2 Answers · Science & Mathematics · 25/04/2011